Spontaneous Regression after Extensive Recurrence of a Pediatric Cervical Spine Aneurysmal Bone Cyst - Carlo Brembilla; Luigi Andrea Lanterna; Michela Bosisio; Paolo Gritti; Andrea Risso; Antonio Signorelli; Francesco Biroli (Case Reports in Oncological Medicine)
Aneurysmal bone cyst is a pseudotumoral lesion. Complete resection prior to selective arterial embolization seems to be the treatment of choice for the more extensive and destructive lesions. In these cases maintaining stability of the cervical spine is critical. This can be very challenging in children and adolescents in whom the axial skeleton is still growing. In this case a young girl presented with a voluminous cervical aneurysmal bone cyst encaging both vertebral arteries and spinal cord. The lesion was treated with aggressive surgical resection, followed by cervical vertebral fusion with instrumentation. After nine months the patient referred no pain and no neurological deficit. MRI scans showed an extensive local recurrence. The family of the young girl refused any other therapy and any other followup. The patients returned to our attention after five years with no pain and neurological deficit. Cervical spine radiographs and MRI scans showed a complete regression of the extensive local recurrence. In the literature, the possibility of spontaneous regression of residual part or local recurrence is reported. The case of this young girl provided the chance to attend a spontaneous regression in an extensive recurrence of aneurismal bone cyst.